2012
DOI: 10.1016/j.bandl.2011.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Stopping speech suppresses the task-irrelevant hand

Abstract: Some situations require one to quickly stop an initiated response. Recent evidence suggests that rapid stopping engages a mechanism that has diffuse effects on the motor system. For example, stopping the hand dampens the excitability of the task-irrelevant leg. However, it is unclear whether this 'global suppression' could apply across wider motor modalities. Here we tested whether stopping speech leads to suppression of the task-irrelevant hand. We used Transcranial Magnetic Stimulation over the primary motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 31 publications
(55 reference statements)
9
64
0
Order By: Relevance
“…The first study along these lines showed that when subjects stopped their hand, there were reduced MEPs from the leg (Badry et al, 2009). This has now been replicated many times for stopping of hands, speech, and even eyes (Cai et al, 2012; Greenhouse et al, 2012; Majid et al, 2012; Wessel et al, In press; Wessel et al, 2013) (FIGURE 4B), also see (Coxon et al, 2006; MacDonald et al, 2014; Sohn et al, 2002) for similar results with related paradigms. Together, these studies clearly show that rapidly stopping one effector broadly affects the skeletomotor system.…”
Section: The Brain’s Network For Global Motor Stoppingsupporting
confidence: 61%
“…The first study along these lines showed that when subjects stopped their hand, there were reduced MEPs from the leg (Badry et al, 2009). This has now been replicated many times for stopping of hands, speech, and even eyes (Cai et al, 2012; Greenhouse et al, 2012; Majid et al, 2012; Wessel et al, In press; Wessel et al, 2013) (FIGURE 4B), also see (Coxon et al, 2006; MacDonald et al, 2014; Sohn et al, 2002) for similar results with related paradigms. Together, these studies clearly show that rapidly stopping one effector broadly affects the skeletomotor system.…”
Section: The Brain’s Network For Global Motor Stoppingsupporting
confidence: 61%
“…In particular, reactive inhibitory control seemed to have a "global" effect on corticomotor excitability (Cai, Oldenkamp, & Aron, 2012;Majid, Cai, George, Verbruggen, & Aron, 2012), whereas proactive inhibitory control was more selective (Majid, Cai, Corey-Bloom, & Aron, 2013). It has been suggested that reactive inhibitory control could be implemented via a hyperdirect pathway between the right IFG and the subthalamic nucleus (Aron et al, 2007), resulting in global inhibition (Majid et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…First, rapid successful motor stopping could induce global suppression that also impacts value. It has already been shown that successful action stopping has global suppressive effects at the motor level (Badry et al, 2009; Cai, Oldenkamp, & Aron, 2012; Majid, Cai, George, Verbruggen, & Aron, 2012; Wessel, Reynoso, & Aron, 2013). Accordingly, successful action stopping could also have a suppressive effect on cognition.…”
Section: Discussionmentioning
confidence: 99%